Utilization of Patchouly Oil as Facial Wash Cosmetic For Acne-Prone Skin - Ramadani, Nesy Fitri; Minerva, Prima (MSJ : Majority Science Journal, 2024)
The research on utilizing patchouli oil as a facial wash for acne-prone skin employs a quantitative approach with an experimental design. Acne issues occur in both females and males aged 17-21. Acne skin care can be addressed using natural-based facial cleansers containing antibacterial ingredients. One natural ingredient that can be used for facial wash is Patchouli leaves, which contain active compounds such as alkaloids, saponins, phenolics, flavonoids, triterpenoids, and glycosides that act as antibacterial agents. The facial wash formulation was designed by varying the concentration of patchouli oil: F1 (1%), F2 (2%), and F3 (3%). Phytochemical screening of the patchouli oil facial wash revealed that F1, F2, and F3 were negative for flavonoids, positive for saponins, and F1 was negative for alkaloids while F2 and F3 were positive. The results showed that the patchouli oil facial wash met the requirements for organoleptic tests, pH tests, homogeneity tests, and foam height tests. Among the various formulations, F3 was found to meet the requirements most effectively.